The locus of power in the European Union: determining whether judicial power will remain at the nation state level or if the European Union will merge into a federal institution - Wesley, Tiffani (Department of Political Studies, 2014)
Larry Backer opines that 'Most of the academic work regarding the "lessons" offered by American federalism for the European Union ("EU") and other supra-national systems has predominantly focused on an understanding of post-Civil War American federalism. It remains, on that account, extremely superficial.' Backer notes that there are important lessons to learn from Calhoun's marginalized understanding of federalism that provide emerging supra-national unions like the European Union with a powerful conceptual foundation for the construction of non-national federal systems of government. The research question seeks to test this debate, first by following the theoretical arguments that took place within the United States on the issue surrounding states' rights versus federalism, and second through the various court cases that have occurred within the European national courts and the European Court of Justice. In essence, the research question seeks to determine where the locus of power currently resides, or will tend to reside, between to the European Union and its member nations.